A Two-Eyed Seeing Teaching and Learning Framework for Science Education - Constance Cirkony; John Kenny; David Zandvliet (2023)
Worldwide, education jurisdictions are looking for authentic ways to address First Nations perspectives in the K-12 curriculum, including science education. At the same time, there have been ongoing efforts to integrate authentic and engaging approaches to teaching science, including those that are student-centred, inquiry-based, multimodal, and linked to meaningful contexts. Both goals may be realised through the principle of Two-Eyed Seeing (TES), which seeks to integrate the strengths of Indigenous ways of knowing with one eye, and Western ways of knowing with the other eye, for the benefit of all students. This theoretical paper presents a Two-Eyed Seeing for Science Education (TESSE) Framework, which brings together two pedagogical models. One is from a contemporary science perspective, the 5Es representation-rich inquiry approach, which scaffolds authentic student-centred conceptually focused learning experiences. The other is from an Indigenous perspective, the 8 Aboriginal Ways of Learning, which illustrates different ways of knowing—many of which are familiar with First Peoples across the world (e.g., place-based, visual, holistic). The TESSE Framework aims to act as a strengths-based interface between the two knowledge systems to support a culturally responsive approach to teaching and learning science. It is designed to support meaningful connections through curriculum and pedagogy in ways that are contextually relevant to place. Through empirical investigation and in collaboration with local communities, the Framework has the potential to inform current approaches to science education in schools and universities and provide a pathway towards decolonisation and reconciliation.